The importance of fiction to the Raffles Library, Singapore, during the long nineteenth-century - Luyt, Brendan (2011)
One of the main controversies in the world of librarianship in the latter half of the nineteenth and early part of the twentieth century was the role of fiction in the public libraries of North America and United Kingdom. To what extent was this concern translated to other parts of the English-speaking world? In this article, I explore, from the available evidence, the attitudes towards fiction held by officials of the Raffles Library, Singapore. I present evidence that the library tended to be very liberal in its views. To understand why this was the case, I argue, involves an understanding of the notion, commonly held at the time, of human degeneration from prolonged exposure to tropical environments, and the colonialist reaction to this predicament.